Juridical Study of Unlawful Acts as Factors in Cancellation of Auctions on Guaranteed Objects - Herry Christian, Jordy (Lex Scientia Law Review, 2019)
The juridical study of onrechtmatige daad as a factor in the cancellation of the auction of mortgage objects guarantees whether there is PMH (onrechtmatige daad) carried out by the creditor against the debtor in carrying out the execution auction of the mortgage object execution. This study is inseparable from article 1365 Burgerlijk Wetboek which was ratified into the Civil Code which contains 4 conditions or elements of onrechtmatige daad, namely that there must be an act (daad), an error (schuld), a loss (shade) and causality (causality). One of the modern arguments often used by debtors to cancel auctions of mortgage objects is the setting of a low value or price limit that is not in accordance with the provisions of the auction. As a real example of setting a limit value or price as a cancelation factor for an auction, we can find it in the Supreme Court Decision No. 274/PDT.G/2013/PN.BDG in which the debtor argues that there was an unlawful act committed by the creditor or the defendant so that the judge declares the auction is illegal and has no binding legal force, this is because the implementation of the auction does not comply with the auction provisions in PMK Number 27/PMK.06/2016, so that the minutes of the auction for the collateral object are canceled by the judge in his decision.